PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Kasus Perusahaan Non Keuangan Peserta Corporate Governance Perception Index tahun 2008-2013) - Novia Ayu Wardhani, 11.05.52.0088; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of corporate governance on corporate performance. This study uses regression analysis to determine whether corporate governance has a positive effect. Sampling Corporate governance Perception Index (CGPI) in 2008 to 2013 from the Indonesian Institute for Corporate governance (IICG) is used to measure the effect of corporate governance with Tobins Q on market performance. This study used a sample of 61 manufacturing companies surveyed IICG from 2008 to 2013, the financial statements of companies listed BEI, and the Indonesian Capital Market Directory (ICMD). Sampling method is purposive sampling. Results from this study indicate that there is a significant positive relationship between corporate governance with Tobins Q, this is because the companies that implement GCG will increase the market value and also provide protection to the shareholders thereby increasing investor confidence will feel safe against investment.Keywords: Corporate Governance, Performance Corporate, and Tobins Q